Assessing the connections between COVID-19 and waste management in Brazil - Leal Filho, Walter (2022)
In addition to the health crisis caused by the coronavirus pandemic, several countries— particularly in developing regions—faced serious additional challenges in the economic, social and environmental areas. In Brazil, one of these challenges refers to the changes in consumption caused by the lockdowns, and the environmental impacts caused by new patterns of waste generation. Against this background, this paper investigates the changes in consumption and waste generation in Brazil during the COVID-19 pandemic. It provides a technical contribution to the topic by comparing the perception of survey respondents on the amount of household waste produced before and during the pandemic, and cross-checking these with information on current aspects of policymaking, the findings suggest that the amount of some specific types of household waste has noticeably increased, challenging even more the local waste management systems. The data instrument was validated by a pre-test, prior to deployment. According to the respondents, packaging (both plastic and paper/cardboard) was the type of waste that reported the highest increase in generation during the lockdowns, which is in line with the results of increased consumption of food delivery within this period. The results also suggest that current waste management policies make Brazil ill-equipped to deal with one of the non-intended effects of the COVID-19 pandemic, which has severely impacted Latin America’s largest country.